Mechanism of Activation of Mechanistic Target of Rapamycin Complex 1 by Methionine - Kitada, Munehiro; Xu, Jing; Ogura, Yoshio; Monno, Itaru; Koya, Daisuke (Frontiers in Cell and Developmental Biology, 2020)
Nutrients are closely involved in the regulation of lifespan and metabolic health. Cellular activities, such as the regulation of metabolism, growth, and aging, are mediated by a network of nutrients and nutrient-sensing pathways. Among the nutrient-sensing pathways, the mechanistic target of rapamycin complex 1 (mTORC1) acts as the central regulator of cellular functions, which include autophagy. Autophagy plays a significant role in the removal of protein aggregates and damaged or excess organelles, including mitochondria, to maintain intracellular homeostasis, which is involved in lifespan extension and cardiometabolic health. Moreover, dietary methionine restriction may have a beneficial effect on lifespan extension and metabolic health. In contrast, methionine may activate mTORC1 and suppress autophagy. As the mechanism of methionine sensing on mTORC1, SAMTOR was identified as a sensor of S-adenosyl methionine (SAM), a metabolite of methionine, in the cytoplasm. Conversely, methionine may activate the mTORC1 signaling pathway through the activation of phosphatase 2A (PP2A) because of increased methylation in response to intracellular SAM levels. In this review, we summarized the recent findings regarding the mechanism via which methionine activates mTORC1.